Bdellovibrio bacteriovorus: a “magic weapon” against bacterial pathogens - Saleh Mohammed Al-maaqar; Abdulaziz Radhi S. Al Johni; Nasser A. Al-Tayyar; Jafar Abdullah Alhamad; Abdullah A. Khan Ghyathuddin; Wael A. Alsubhi; Ammar AL-Farga; Nahid Kamal Eldin; Hala Mohammad Marouf; Mohsen A. Khormi (Annals of Microbiology)
Abstract Background Antimicrobial resistance is one of the most pressing global health threats of the twenty-first century. Bacterial infections linked to multidrug resistant bacteria are quickly spreading, and they constitute a very serious threat to human life. The search for new types of antibiotics to overcome resistance has plateaued for over two decades, and current development pipelines rely predominantly on structural derivatives. This approach has not evolved as rapidly as resistance and therefore, there is need to develop new therapeutic strategies. Natural therapeutic agents are considered as a suitable source of novel antimicrobials because they have high antimicrobial efficacy, and they select different targets in comparison to traditionally used antimicrobials. Objective and main body. This work reviews the biology and natural predator characteristics of Bdellovibrio bacteriovorus (B. bacteriovorus) and its applications. It also highlights the challenges associated with its use and explores future research directions. B. bacteriovorus, are promising therapeutic agents combating multidrug resistant bacterial infections. B. bacteriovorus is predatory bacterium, which is known by its obligate parasitic mode of life in which it can rely solely on preying on other bacteria. B. bacteriovorus predator behavior allows the agent to adhere to the surface of host bacteria, piercing the cell wall and then invading the host’s periplasmic space where it propagates causing lysis and release of progeny. B. bacteriovorus inhabits a wide range of ecological settings, including soil and freshwater habitats, where it plays a crucial ecological role in regulating bacterial populations. Conclusion The applications of B. bacteriovorus go beyond medical uses to agriculture, food safety interventions and wastewater treatment as well. Despite the diverse use of B. bacteriovorus, additional research is necessitated to maximize the formulation strategies, and delivery means for efficient and proper practical use.